Impact of age and body mass index on dual-energy X-ray absorptiometry scan results in postmenopausal women - Halil Ćorović; Nusret Salkica; Naida Omerović Ćorović; Šejla Cerić; Selma Agić-Bilalagić; Amra Skopljak-Beganović; Enis Tinjak (Medicinski glasnik, 2025)
Aim: To analyse the impact of age and body mass index (BMI) on dual-energy X-ray absorptiometry (DXA) scan results in postmenopausal women. Methods: The study included 100 postmenopausal women who underwent the DXA procedure, out of which 50 had a normal BMI and 50 were overweight/obese. Data that were examined included age, BMI, T-score of the lumbar region and the femoral neck, as well as bone mineral density (BMD). Correlation results were presented as Pearson’s correlation coefficient (r). Results: The T2-score and BMD2 were significantly lower in older patients compared to younger ones (p=0.008 and p=0.007, respectively). Post hoc test results showed that the T2-score and BMD2 were significantly lower in patients ?71 years of age compared to patients ?59 years of age (p=0.006 and p=0.005, respectively). Also, T1- and T2-scores, as well as BMD1 and BMD2, were significantly higher in overweight/obese patients (p<0.001 and p=0.003; p<0.001 and p=0.002, respectively). The correlation between BMI and the T1-score was moderate (r=0.429), between BMI and the T2-score weak (r=0.348), between BMI and BMD1 moderate (r=0.431), and between BMI and BMD2 weak (r=0.344). Conclusion: Our study showed that both age and BMI are important factors affecting DXA procedures and should be taken into account with each postmenopausal woman individually in everyday practice.
Keywords: body weight; densitometry; postmenopause